Construction of A Small Semi-automatic Orthogonal Cutting Blade Plam Chopper - พูนนายม ปราโมทย์; แย้มเผื่อน ไพบูลย์; วัฒนจิตสิริ วรญา; ตรันวนพงศ์ สุรัตน์; กิมะพงศ กิตติพงษ์ (Frontiers in Engineering Innovation Research, 2018)
Palm is important crops that could solve an energy shortage problem in Thailand, had a high planting area and also had high volume grow in nationwide. Therefore, a management of a palm planting area should be effectively done for a required productive amount. High cutting palm branch amount was one of current problems that were required to degrade or utilize but it was difficult to operate because of a limit of a large cutting machine movement in a planting area. Such reasons, this project aimed to design and construct of a small semi-automatic orthogonal cutting blade that could adjust the cutting parameter such as a rotating speed of cutting blades, a cutting blade number, a cutting clearance and a palm feeding angle. The machine efficient test could be performed by a weight measurement and a dimension measurement of a palm cutting scrap. The summarized results are as follows. The dimension of the palm chopping machine that was designed and constructed was 1000 millimeters in width, 1000 millimeters in length and 1000 millimeters in high. The machine could operate under the rotating speed of 100-1000 rpm, the cutting blade of 2-6 blades, the feed distance of 0.5-3.0 millimeters and the tilted feed angle of 0-45 degrees. The cutting speed that produced a maximum chip production amount of 3,881 g/min and the average chip morphology of 31.38 millimeters in thickness, was 1000 rpm. The thickness of the cutting chip that were obtained in this experiment were decreased when the rotating speed of the cutting plate was increased. Furthermore, the increase of the rotating speed of the cutting plate directly affected to increase the palm chip production amount